‘I gotta Feeling’: Exploring the effects of a smartphone app (Feelee) to enhance adolescents’ emotion regulation in forensic outpatient settings: A multiple single-case experimental design - Merel M. L. Leijse; Levi van Dam; Samantha Bouwmeester; Thimo M. van der Pol; René Breuk; Arne Popma (PLoS ONE, 2026)
Adolescents in forensic outpatient care often face a complex interplay of emotional and cognitive challenges, which is also reflected in current challenges within treatment approaches. Mobile health (mHealth) interventions have shown increasing value in forensic settings, although empirical evidence remains limited. One particular mHealth app that may address current challenges in forensic outpatient care is Feelee, which provides daily emotion regulation practice through self-reported emotional check-ins and passively collected smartphone sensor data. Given the potential but still limited evidence for mHealth apps in forensic settings, this study aimed to provide first thorough evaluation of the Feelee app as an addition to treatment as usual to enhance emotion regulation skills among adolescents in forensic outpatient care. A multiple single-case experimental ABA design was applied, consisting of a 2-week baseline (phase A 1 ), 4-week intervention (phase B), and 2-week follow-up (phase A 2 ), combining quantitative and qualitative methods. Twenty-two adolescents (aged 12–23) completed daily assessments of emotion regulation. Secondary outcomes focused on emotional developmental mechanisms and treatment-related factors, measured at pre-, post-, and follow-up. Semi-structured interviews with adolescents and clinicians explored experiences with Feelee and its integration into treatment. Results showed a significant improvement in the emotional recognition during the intervention phase. No improvements were found in emotion suppression and impulse control, while reflection and distraction showed reversed outcomes. At follow-up, secondary outcomes indicated increases in positive emotion differentiation, emotional awareness, and self-reflection. Treatment motivation remained stable, while therapeutic alliance improved. Qualitative findings highlighted increased emotional insight, a alongside technical difficulties and limited discussion of Feelee data during sessions. These findings suggest that Feelee may particularly be valuable in the early stages of emotion regulation by enhancing emotional recognition. Future research should explore longer-term use and actively involve clinicians in the integration of app data to maximize therapeutic relevance and impact. Trial registration Central Committee on Research Involving Human Subjects NL-OMON54390 and ClinicalTrials.gov NCT06509360